2011
DOI: 10.1143/jjap.50.06ge01
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Ultrahigh-Density Magnetic Nanowire Arrays beyond 1 Terabit/Inch2 on Si Substrate Using Anodic Aluminum Oxide Template

Abstract: Ultrahigh-density Co nanowire arrays were fabricated by the combined use of the anodic aluminum oxide (AAO) template formed on a Si substrate and pulse DC electrodeposition. The AAO templates were prepared with the anodic voltages from 3 to 40 V, whose diameters were from 15 to 40 nm. Using the AAO template with an anodic voltage less than 3 V, the wire density exceeded 2.88 Tbit/in. 2 . The magnetic property of the nanowire arrays indicated a strong perpendicular magnetic anisotropy, and we observed the tende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…The coercivity of magnetic nanowires has been found to increase as the diameter of the wires decreases. 9,13,14 In our modulated wires, compared to the straight wires of the smaller diameter, the wires have segments with wider diameters that tend to reduce the coercivity.…”
Section: Resultsmentioning
confidence: 99%
“…The coercivity of magnetic nanowires has been found to increase as the diameter of the wires decreases. 9,13,14 In our modulated wires, compared to the straight wires of the smaller diameter, the wires have segments with wider diameters that tend to reduce the coercivity.…”
Section: Resultsmentioning
confidence: 99%
“…It was concluded that these segmented structures can be applied for high-density magnetic storage devices showing a bit density of up to 70 Gbits/in 2 . Even higher bit densities of ~3 Tbit/in 2 were achieved by electrodeposited Co nanorods, which prove the potential of electrodeposited magnetic nanorods for data storage applications [ 149 ].…”
Section: Nickel Nanorod Applicationsmentioning
confidence: 99%
“…A 10-µm thick nanotruss structure was grown on a lightweight, flexible and conducting carbon-paper substrate, which enabled the efficient production of H2 gas from water splitting at a low overpotential of 210 mV and at a current density of 10 mA/cm 2 . Keywords: nanotrusses, nanowires, nanoparticles, iron, electrocatalysis, pulsed sputtering Solution-based magnetic self-assembly of in situ or ex situ synthesized ferromagnetic nanoparticles is currently a vibrant field [1][2][3][4][5][6][7][8][9] , partially since the resulting nanostructures promise important or improved application in energy storage 10,11 , chemical production 12 , and ultra-highdensity magnetic storage 13 . A drawback with this solution-based approach is the difficulty in keeping the nanoparticles clean from oxides and other impurities, and that the inter-particle contacts and resulting nanostructures consequently suffer in both stability and electrical conductivity.…”
mentioning
confidence: 99%